Improved The Emphaty Through Techniques Photovoice In Family Dusun Alas Timur Bawean Gresik - Wenti Krisnawati; Eka Wahyu Nur; Dzuhriawan Farrikh (OJS Universitas Muhammadiyah Gresik, 2020)
Most people who live on Bawean Island go abroad to earn a living and study. so they must be willing to leave their families to achieve their coveted dreams. Often the nomads' family will miss him and vice versa the nomads also miss his family. What is unexpected is that in most homes, family photographs are rarely found, even though their benefits can be used as medicine if they miss family members who are migrating. Therefore, the presence of family photos is expected to increase empathy which indicates harmony in a family. This program was carried out on August 24, 2019 by visiting residents' homes in accordance with the agreed time during the survey in advance.